극저온 환경의 인쇄기판형 열교환기 열적성능에 대한 실험적 연구 - 김동호(Dong Ho Kim); 나상준(Sang Jun Na); 김영(Young Kim); 최준석(Jun Seok Choi); 윤석호(Seok Ho Yoon) (설비공학 논문집, 27(8), 2015)
The advantages of a printed circuit heat exchanger (PCHE) are the compactness and efficiency derived from its heat-transfer characteristics; furthermore, a PCHE for which a diffusion bonding method was used during production can be applied to extreme environments such as a cryogenic condition. In this study, a micro-channel PCHE fabricated by diffusion bonding was investigated in a cryogenic environment regarding its thermal performance and the pressure drop. The test rig consists of an LN2 storage tank, vaporizers, heaters, and a cold box, whereby the vaporized cryogenic nitrogen flows in hot and cold streams. The overall heat-transfer coefficients were evaluated and compared with traditional correlations. Lastly, we suggested the modified heat-transfer correlations for a PCHE in a cryogenic condition.